2013
DOI: 10.1124/dmd.112.049429
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Four New Mouse Cytochrome P450 Enzymes of the CYP2J Subfamily

Abstract: The cytochrome P450 superfamily encompasses a diverse group of enzymes that catalyze the oxidation of various substrates. The mouse CYP2J subfamily includes members that have wide tissue distribution and are active in the metabolism of arachidonic acid (AA), linoleic acid (LA), and other lipids and xenobiotics. The mouse Cyp2j locus contains seven genes and three pseudogenes located in a contiguous 0.62 megabase cluster on chromosome 4. We describe four new mouse CYP2J isoforms (designated CYP2J8, CYP2J11, CYP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 48 publications
5
29
0
Order By: Relevance
“…It is clear that many additional P450 isoforms remain to be studied in the context of opioid analgesia. Among these, members of the CYP4X (Iliff et al, 2010) and CYP2J (Graves et al, 2013) subfamilies have epoxygenase activity and are found in the CNS. Although the P450 epoxygenase hypothesis has not been confirmed, new classes of analgesic or antihyperalgesic medications are already being developed to mimic the actions of lipid epoxides (Brostram and Falck, 2013) or to inhibit their metabolism (Wagner et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that many additional P450 isoforms remain to be studied in the context of opioid analgesia. Among these, members of the CYP4X (Iliff et al, 2010) and CYP2J (Graves et al, 2013) subfamilies have epoxygenase activity and are found in the CNS. Although the P450 epoxygenase hypothesis has not been confirmed, new classes of analgesic or antihyperalgesic medications are already being developed to mimic the actions of lipid epoxides (Brostram and Falck, 2013) or to inhibit their metabolism (Wagner et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Specific primer sets of oligonucleotides were designed, spanning exon/exon boundaries if possible, for the mouse Cyp2j subfamily members (Table 2). Some primer sets were those that had previously been published for use in nonquantitative RT-PCR Graves et al, 2013). All primers were diluted to a concentration of 10 mM, and 0.5 ml was used in a total volume of 10 ml for the qPCR reactions.…”
Section: Methodsmentioning
confidence: 99%
“…Mouse Cyp2j subfamily members are active in the metabolism of AA and other substrates Qu et al, 2001;Ma et al, 2002;Graves et al, 2013). The majority of P450 enzymes are abundantly expressed in the liver, but the mouse Cyp2j subfamily members are predominantly found in extrahepatic tissues.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations